Peculiarities of identification of persons who died during martial law (literature review) - Biliakov, A.M.; Erhard, N.M. (Medicni Perspektivi, 2023)
Identification of dead persons in forensic medical practice is key one during the martial law in Ukraine. Nowadays, when new research methods and modern laboratory and instrumental equipment appear, there is a need to improve forensic diagnostics during the identification of unknown persons. The goal was to establish the peculiarity of the identification of dead persons during martial law, to provide practical recommendations for the selection and extraction of biological material during forensic medical examinations of corpses. The reliability of the results and conclusions is ensured by the use of general scientific empirical and theoretical research methods. With the help of the general scientific methods of research (analysis, synthesis, generalization), scientific and informational literary sources by the subject of research are characterized. The level of problematic issues in the profile information was determined and recommendations for solving problematic aspects related to the identification of dead persons were provided. A systematic approach to solving problematic issues made it possible to formulate conclusions to achieve the set goal. The necessity of training experts in the peculiarities of material selection for further DNA identification is substantiated. The need to provide forensic medical experts with the necessary consumables and equipment, as well as urgent revision of the normative acts regulating their activities, has been proven. The features of identification of putrefied persons are characterized, which consist in the possibility of DNA extraction from smears from the wall of the aorta, the wall of the urinary bladder, brain tissue and intact teeth. It is proven that the identification of dead persons during the martial law is complicated by the influence of the thermal factor, as well as pronounced putrefactive changes. In these cases, bones and teeth as the objects of DNA extraction should be preferential. The relevance and practical significance of the use of innovative technologies for the identification of dead persons during martial law have been established. Some issues of regulatory and legal provision of forensic medical identification of dead persons during martial law, the need to improve the procedure for taking biological samples in criminal proceedings, etc. were raised. Directions for their solution are proposed.